EFFECTS OF DATE PALM POLLEN EXTRACT (PHOENIX DACTYLIFERA L.) ON REPRODUCTIVE FUNCTION IN RATS - Musab Abdelrahim; Elhadi Ahmed; Imad Taj-Eldin; Abd-Elwahab Mohammed (International Journal of Pharmacy & Integrated Health Sciences, 2025)
Background: Plant materials represent a significant source in traditional medical practices for treating many disorders. However, many pharmacological studies have provided the basis for their therapeutic potential. Objectives: This work aimed to assess the effects of the methanolic extract of date palm pollen on some fertility parameters in rats. Methodology: Experiments were performed using conventional methods for extraction of plant material (by methanolic maceration) and for fertility testing in rats. Twenty sexually mature rats were tested in the current study (10 males and 10 female rats) for 28 days. The animals were allocated to control and test groups of males and females (5 animals/group). The control groups of males and females were administered with distilled water, whereas the test groups received daily oral doses of the plant extract at 250 mg/kg. Results: The animals were sacrificed at the end of the study to determine the fertility parameters. The results showed that the plant material exhibited an estrogenic property, as evidenced by the significant elevation of estradiol serum levels in both sexes. Moreover, epididymal sperm count showed a significant elevation in the test group of male animals compared to the control group of male animals. Conclusion: These findings could support and validate the ethnomedicinal uses of the plant material in treating some male fertility disorders and could provide a candidate source for drug development.